Cinema statistics in Saorstat Eireann - Beere, Thekla J. (Statistical and Social Inquiry Society of Ireland, 1936)
For some time the idea of undertaking a preliminary survey of the Cinemas in the Saorstat had kept recurring to me, but it was not until last December that I was finally stimulated to action by Mr Rowson's most valuable paper entitled "A Statistical Survey of the Cinema Industry of Great Britain in 1934," read before the Royal Statistical Society. I should like to acknowledge my indebtedness to this paper for several lines of approach which might never otherwise have occurred to me and also for certain figures relating to Cinemas in England, Scotland and Wales, which have provided interesting and illuminating comparisons.
Read before Society on Thursday, the 28th May, 1936
Keywords: Cinema statistics; Cinema attendance; Censorship; 314.15